2013
DOI: 10.1097/qai.0b013e318288b246
|View full text |Cite
|
Sign up to set email alerts
|

Social Network–Based Recruitment Successfully Reveals HIV-1 Transmission Networks Among High-Risk Individuals in El Salvador

Abstract: Objective HIV in Central America is concentrated among certain groups such as men who have sex with men (MSM) and female sex workers (FSW). We compared social recruitment chains and HIV transmission clusters from 699 MSM and 757 FSW to better understand factors contributing to ongoing HIV transmission in El Salvador. Methods Phylogenies were reconstructed using pol sequences from 119 HIV-positive individuals recruited by respondent driven sampling (RDS) and compared to RDS chains in three cities in El Salvad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
0
17
0
1
Order By: Relevance
“…In this study, persons were more likely to be in clusters if they were age 30 or younger, had acute infection, were local residents, and contracted drug resistant HIV, but were not Latino. Clustering factors in an El Salvador study [75] were recent infection, sex with stable male partners, and sex with over two partners in the past year. A Hong Kong study [77] of recently HIV-infected MSM employed both phylogenetic and social network analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, persons were more likely to be in clusters if they were age 30 or younger, had acute infection, were local residents, and contracted drug resistant HIV, but were not Latino. Clustering factors in an El Salvador study [75] were recent infection, sex with stable male partners, and sex with over two partners in the past year. A Hong Kong study [77] of recently HIV-infected MSM employed both phylogenetic and social network analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying these persons, regardless of whether they were previously known to surveillance, allows field workers to contact them, ensure linkage or return to care, elicit and notify partners, and expand the network of persons in the city that are receiving public health services. For example, 15.3% (81/448) of named partners in the genetic network linked only to someone other than the index case who named them; therefore, it is possible that simply being a named partner indicates an elevated risk status and possibly increased importance in the network (i.e., an intervention-worthy case) [26, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Such findings suggest a need for setting-specific interventions with heightened attention to those who cross social boundaries. Likewise, a study in El Salvador found that respondent driven sampling methods were successful for identifying MSM transmission networks and that MSM who were in phylogenetic clusters were more likely to report larger social networks of MSM compared to those not in clusters (29). This study suggests that social network and phylogenetic strategies can together help to refine intervention targeting and contact with those at increased risk for transmission.…”
Section: Integrating Hiv Phylogenetics To Understand Characteristics mentioning
confidence: 99%